Point-of-Care Ultrasound May Reduce Misdiagnosis of Pediatric Intussusception - Hsiao, Hsiang-Ju; Wang, Chao-Jan; Lee, Chien-Chung; Hsin, Yi-Chen; Yau, Sze-Yuen; Chen, Shih-Yen; Lo, Wan-Chak; Wu, Patricia-Wanping; Chen, Chyi-Liang; Chang, Yi-Jung (Frontiers in Pediatrics, 2021)
Aim Intussusception, the most common abdominal emergency in early childhood, is frequently misdiagnosed at initial presentation. The effect of using point-of-care ultrasonography (POCUS) by emergency medicine physicians on pediatric intussusception misdiagnosis rate remains unclear. Here, we summarize outcomes and misdiagnoses before and after training junior and senior physicians on using POCUS for diagnosing intussusception and compared their performance levels. Materials and Methods This observational cohort analysis included patients with suspected intussusception who visited a pediatric emergency department (ED) between January 2017 and December 2019. All enrolled patients were evaluated by junior (<10-year experience) or senior attending physicians. Misdiagnosis was defined as a finding of negative air reduction or confirmation of diagnosis on ED revisit or admission. The misdiagnosis rates and outcomes before and after POCUS training for intussusception diagnosis were evaluated and performance of the junior and senior physicians was compared. Results Of the 167 enrolled patients, 130 were confirmed to have intussusception by air reduction. Misdiagnosis rate was significantly lower in the posttraining patient group after training than in the pretraining patient group (43.7% vs. 12.7%, P < 0.001). After training, fewer misdiagnoses were made by the junior (59.1% vs. 25.9%, P = 0.003) and senior (31.7% vs. 0%, P < 0.001) physicians. In the posttraining patient group, the door-to-reduction time and rate of ultrasonography consultation with an expert also decreased significantly (118.2 ± 124.5 vs. 198 ± 250.2 min, P = 0.006). Abdominal pain (80.9%) was the most common symptom of intussusception, followed by vomiting (58.3%), fever (17.8%), bloody stool (15.4%), and diarrhea (14.2%). Even after training, the presenting symptoms of intussusception often leading junior physicians to misdiagnosis were diarrhea and fever. Conclusions A brief POCUS training leads to decreased misdiagnosis rates in both the senior and junior physicians. Junior physicians should increase their awareness regarding diarrhea and fever being the presenting symptoms of intussusception, particularly in early childhood. Combining clinical judgment and POCUS results form the core principle of the evaluation of children with intussusception.